Application of Two-Stage Network Super-Efficiency DEA to Efficiency Analysis of Chinese Commercial Banks - Qingquan Li; Shiqi Chen; Lu He; Guohui Huang; Rong Li; Wentsao Pan (Journal of Mathematics)
Commercial banks occupy an important leading position in China’s banking industry, and their efficiency is of great reference value to the economy of China’s financial system, reflecting the current state of China’s economy. In this paper, the super-efficiency DEA values of 19 commercial banks from 2016 to 2020 are calculated by employing the super-efficiency method into the two-stage network DEA model with constant returns to scale. Compared with the traditional two-stage network DEA model, this method is better. The results show that the calculated values are more accurate than the DEA values measured directly by the two-stage network, and the banks with an efficiency value of 1 can be further distinguished. According to the analysis of table data, the operating efficiency of ICBC is the highest, the operating efficiency of the entire banking sector is at a medium level, the second stage has a greater impact on the overall efficiency, and the loan side business needs to be improved.